Flower-like NiO nano magnetic bead as well as preparation method and application thereof
By depositing NiO nanoflower cladding on Fe3O4 magnetic nanoparticles in situ, flower-like Fe3O4@NiO nanoparticles were prepared, which solved the problems of complex preparation methods for existing composite magnetic nanoparticles and low adsorption capacity, and achieved rapid, efficient and specific separation and purification of proteins, and excellent adsorption capacity and recycling performance.
Patent Information
- Application Number
- CN202411739086.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing preparation methods for composite magnetic nanoparticles are complex, with low specificity and low adsorption capacity, making it difficult to meet the needs of protein separation and purification.
By depositing NiO nanoflower cladding on Fe3O4 magnetic nanoparticles in situ, flower-like Fe3O4@NiO nanoparticles were prepared, and the targeted binding ability of their endogenous Fe3O4 magnetic core and NiO cladding was used to achieve rapid, efficient and specific separation and purification of proteins.
The efficient separation and purification of His-tagged fusion protein was achieved, with an adsorption capacity of 65.83 mg/g. The separation efficiency was still higher than 80% after recycling. The preparation method was simple and suitable for large-scale production.
Smart Images

Figure CN119591166A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic nano materials and bioanalysis, and in particular relates to a method for preparing nano magnetic beads. Background Art
[0002] Traditional protein separation and purification methods include electrophoresis, chromatography, centrifugation, dialysis, filtration, etc., among which metal chelate affinity chromatography is considered to be one of the most effective methods. Although metal chelate affinity chromatography has many advantages in the separation and purification of histidine-tagged proteins, it still has problems such as low efficiency, high cost, and cumbersome separation and purification steps, which makes it impossible to meet the separation requirements. The combination of metal chelate affinity chromatography and magnetic separation technology for protein separation and purification has become a research hotspot in biomedical research and bioengineering technology. It is achieved by surface modification of magnetic nanoparticles, coupling with ligands that can be bound by target proteins, and using an external magnetic field to separate and purify proteins. This method has the advantages of simple operation, rapidity, efficient enrichment, and high reusability.
[0003] At present, some composite magnetic nanoparticles for separation and purification of target proteins have been developed. For example, a composite magnetic nanoparticle Fe3O4 / MPS / PPA / NTA-Ni is disclosed in publication number CN105837766A. 2+ The Fe3O4 magnetic nanoparticles were modified to be rich in double bonds, and then coated with PAA to give them a multi-hydroxy structure. 2+ The preparation method of the composite magnetic nanoparticles is relatively complicated, and it needs to go through multiple steps of modification to achieve the binding of the target protein. For another example, the application with publication number CN115504515A discloses a magnetic responsive nanomaterial based on magnetic nano γ-Fe2O3@Al2O3 and its preparation method and application, but when it is used for adsorption and enrichment of His-tagged fusion protein, its enrichment capacity is only 45.03 mg / g, and the adsorption capacity is not high. Summary of the invention
[0004] The present invention provides flower-like NiO nanomagnetic beads and a preparation method and application thereof, which solve the technical problems in the prior art of complex preparation method of composite magnetic particles, low specificity, low adsorption capacity, etc.
[0005] The technical solution of the present invention is achieved in this way:
[0006] The preparation method of flower-like NiO nanomagnetic beads comprises the following steps:
[0007] (1) Fe3O4 and NiCl2·6H2O are dispersed in distilled water, and ammonia water is added. The mixture is stirred at room temperature and then stirred and heated to react. The reaction liquid is separated and the bottom product is collected.
[0008] (2) The bottom product of step (1) is washed, dried and then calcined to obtain flower-like NiO nanomagnetic beads, namely Fe3O4@NiO nanoparticles (Fe3O4@NiO nanoadsorbents).
[0009] In the above step (1), the molar ratio of NiCl2·6H2O to Fe3O4 is 1:(0.3-1.4), and 0.005-0.03 mol Fe3O4 is added per liter of distilled water.
[0010] Furthermore, 0.015-0.075 mol of aqueous ammonia is required to be added for every 1 mmol of NiCl2·6H2O.
[0011] The stirring and heating reaction in the above step (1) is carried out at a temperature of 25-90° C. and a time of 0.5-6 h.
[0012] In the above step (2), the calcination temperature is 380-400° C. and the calcination time is 2-3 hours.
[0013] Flower-like NiO nanomagnetic beads were prepared using the above-mentioned preparation method.
[0014] Application of the above-mentioned flower-like NiO nanomagnetic beads in separation and purification of His-tagged fusion proteins.
[0015] Furthermore, the above separation and purification steps are: adding flower-like NiO nanomagnetic beads to the mixed protein, incubating and magnetically separating, separating the flower-like NiO nanomagnetic beads bound to the His-tagged fusion protein, and eluting with an eluent solution to obtain the His-tagged fusion protein.
[0016] Furthermore, the mass ratio of the above-mentioned flower-like NiO nanomagnetic beads to the mixed protein is 1:(0.015-0.09).
[0017] Further, the incubation temperature is 4-8°C, and the time is 5-90 min. For example, the temperature of low-temperature incubation is 4-6°C, and the time is 30-90 min; for example, the temperature of low-temperature incubation is 6-8°C, and the time is 5-30 min; for example, the temperature of low-temperature incubation is 4-7°C, and the time is 5-90 min; for example, the temperature of low-temperature incubation can be 4°C, 5°C, 6°C, 7°C or 8°C, and the time is 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or 90 min.
[0018] The present invention has the following beneficial effects:
[0019] (1) The present invention proposes a novel magnetic nanocomposite material, which uses ferroferric oxide as an endogenous magnetic core and uses a liquid phase chemical method to in situ deposit a NiO nanoflower coating layer under alkaline conditions to obtain Fe3O4@NiO nanoparticles. Thanks to its endogenous Fe3O4 magnetic core, Fe3O4@NiO nanoparticles can achieve rapid magnetic separation under an external magnetic field; and NiO can produce targeted binding with His-tagged fusion proteins, and after elution, the target protein can be quickly, efficiently, and specifically separated and purified.
[0020] (2) When the Fe3O4@NiO nanoparticles prepared after optimizing the conditions of the present invention are used to separate and purify His-tagged proteins, the separation and purification performance of the target protein is averaged by gel electrophoresis, quantitative detection of protein concentration, etc., indicating that it has good specificity, good universality and recycling performance. The NiO nanoflower coating layer on the surface of the nanoparticles has a unique flower-like structure, which greatly increases the specific surface area of the Fe3O4@NiO nanoadsorbent and reduces the steric hindrance of the target protein during targeted binding, thereby increasing the adsorption capacity of the nanomagnetic beads for the target protein (the saturated adsorption capacity for the His-tagged fusion protein is 65.83 mg / g), and the adsorption capacity is better than that of the commercial products used under the same comparative experimental conditions. And after the Fe3O4@NiO nanoadsorbent is used for 5 times, its separation efficiency for the target protein is still higher than 80%.
[0021] (3) The synthesis method of Fe3O4@NiO nanoparticles proposed in the present invention is simple, and the target nanomagnetic beads can be obtained by in-situ deposition in one step without further surface modification, which will be conducive to large-scale production in practical applications. Moreover, the small-scale test phase of Fe3O4@NiO nanoparticles as nanoprotein purification agents has been completed, and pilot tests are underway, with good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 SEM images of Fe3O4@NiO nanoparticles prepared at different molar ratios of NiCl2·6H2O and Fe3O4; among them, (a) 0; (b) 1:0.3; (c) 1:0.6; (d) 1:0.9; (e) 1:1.2 and (f) 1:1.4.
[0024] Figure 2 SEM images of Fe3O4 and Fe3O4@NiO nanoparticles prepared at different reaction temperatures; (a) Fe3O4; (b) 25℃; (c) 30℃; (d) 50℃; (e) 70℃ and (f) 90℃.
[0025] Figure 3 SEM images of Fe3O4 and Fe3O4@NiO nanoparticles prepared under different reaction times; among them, (a) is Fe3O4; (b) 0.5h; (c) 1.0h; (d) 2.0h; (e) 4.0h and (f) 6.0h.
[0026] Figure 4 SEM images of Fe3O4@NiO nanoparticles prepared with Fe3O4 and different amounts of ammonia water added; among them, (a) Fe3O4; (b) 0.015 mol; (c) 0.030 mol; (d) 0.045 mol; (e) 0.060 mol and (f) 0.075 mol.
[0027] Figure 5 TEM images of Fe3O4 and Fe3O4@NiO and element surface distribution map of Fe3O4@NiO; (a) is the TEM image of Fe3O4; (bc) are TEM images of Fe3O4@NiO at different magnifications; (de) is the element surface distribution map of Fe3O4@NiO.
[0028] Figure 6 XRD spectra (a), TG curves (b) and FTIR spectra (c) of Fe3O4, Fe3O4@Ni(OH)2 and Fe3O4@NiO.
[0029] Figure 7 (a) The full XPS spectrum of Fe3O4@NiO and the high-resolution XPS spectra of (b) O 1s, (c) C 1s, (d) Fe 2p and (e) Ni2p.
[0030] Figure 8 Hysteresis loops of Fe3O4 and Fe3O4@NiO (a), N2 adsorption-desorption curves of Fe3O4@NiO (b) and pore size distribution diagram (c).
[0031] Fig. 9 The adsorption performance and adsorption kinetic model of Fe3O4@NiO nanoadsorbent for His-tagged GFP protein; (a) is the adsorption amount-concentration curve; (b) is the adsorption amount-time curve; (c) is the simulation analysis results of the pseudo-first-order kinetic model and (d) the pseudo-second-order kinetic model.
[0032] Fig.10 SDS-PAGE images (ac) and corresponding Western blot images (df) of the complexes obtained by separating different His-tagged proteins using Fe3O4@NiO nanoadsorbent; wherein, (a) lane 1, marker; lane 2, His-tagged KAI2 Escherichia coli lysate; lane 3, protein purified by commercial gel nickel column; lane 4, protein purified by Fe3O4@NiO; (b) lane 1, marker; lane 2, His-tagged GFP Escherichia coli lysate; lane 3, protein purified by commercial gel nickel column; lane 4, protein purified by Fe3O4@NiO; (c) lane 1, marker; lane 2, His-tagged PYL3 Escherichia coli lysate; lane 3, protein purified by commercial gel nickel column; lane 4, protein purified by Fe3O4@NiO; (df) are Western blot images corresponding to the SDS-PAGE images of (ac), respectively.
[0033] Fig.11 The figure shows the recycling performance of Ni NPs nanoadsorbents; wherein, (a) is the SDS-PAGE image of repeated use of Fe3O4@NiO nanoadsorbent to separate His-tagged GFP protein; lane 1, first use; lane 2, second use; lane 3, third use; lane 4, fourth use; lane 5, fifth use; lane 6, marker; lane 7, Escherichia coli lysate containing His-tagged GFP; lane 8, protein eluted from a commercial gel nickel column; (b) is the purification ability of Fe3O4@NiO nanoadsorbent to repeatedly separate His-tagged GFP protein. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Unless otherwise specified, the experimental methods used in the following experimental examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0036] Example 1
[0037] The molar ratio of NiCl2·6H2O to Fe3O4 was adjusted to 1:0.3, 1:0.6, 1:0.9, 1:1.2 and 1:1.4, and a series of preparation experiments were carried out to investigate the effect of the molar ratio of NiCl2·6H2O to Fe3O4 on the morphology of the Fe3O4@NiO product. The specific preparation process is as follows:
[0038] 0.3mmol, 0.6mmol, 0.9mmol, 1.2mmol, 1.4mmol of Fe3O4 and 1.0mmol of NiCl2·6H2O were added to 60mL of distilled water, and after dispersion, 0.06mol of ammonia water (1 drop / second) was slowly added thereto; after the addition was completed, the mixture was stirred at room temperature for 30min, and then heated to 70℃ and reacted for 4h under mechanical stirring (400 rpm). After the reaction was completed, magnetic separation was performed, and the bottom product was washed with distilled water 3 times and freeze-dried for 24h. The dried powder was placed in a muffle furnace and calcined at 400℃ for 2h to obtain Fe3O4@NiO nanoparticles ( Figure 1 ).
[0039] Example 2
[0040] The reaction temperatures were controlled at 25°C, 30°C, 50°C, 70°C and 90°C, and a series of preparation experiments were carried out to explore the effect of reaction temperature on the morphology of Fe3O4@NiO products. The specific preparation process is as follows:
[0041] 1.2mmol of Fe3O4 and 1.0mmol of NiCl2·6H2O were added to 60mL of distilled water, and 0.060mol of ammonia water (1 drop / second) was slowly added thereto after dispersion, for a total of 5 groups of experiments; after the addition was completed, the mixture was stirred at room temperature for 30min, and then heated to 25℃, 30℃, 50℃, 70℃ or 90℃ for 4h under mechanical stirring (400 rpm). After the reaction was completed, magnetic separation was performed, and the bottom product was washed 3 times with distilled water and freeze-dried for 24h. The dried powder was ground and placed in a muffle furnace and calcined at 380℃ for 3h to obtain Fe3O4@NiO nanoparticles ( Figure 2 ).
[0042] Example 3
[0043] The reaction time was controlled to be 0.5h, 1.0h, 2.0h, 4.0h and 6.0h respectively, and a series of preparation experiments were carried out to explore the effect of reaction time on the morphology of Fe3O4@NiO products. The specific preparation process is as follows:
[0044] 1.2mmol of Fe3O4 and 1.0mmol of NiCl2·6H2O were added to 60mL of distilled water, and after dispersion, 0.060mol of ammonia water (1 drop / second) was slowly added thereto, for a total of 5 groups of experiments; after the addition was completed, the mixture was stirred at room temperature for 30min, and then heated to 70℃ under mechanical stirring (400 rpm) for reaction for 0.5h, 1.0h, 2.0h, 4.0h or 6.0h respectively. After the reaction was completed, magnetic separation was performed, and the bottom product was washed 3 times with distilled water and freeze-dried for 24h. The dried powder was ground and placed in a muffle furnace, and calcined at 390℃ for 2.5h to obtain Fe3O4@NiO nanoparticles ( Figure 3 ).
[0045] Example 4
[0046] The amount of ammonia added was controlled to be 0.015 mol, 0.030 mol, 0.045 mol, 0.060 mol, and 0.075 mol, and a series of preparation experiments were carried out to investigate the effect of the pH value of the reaction system on the morphology of the synthesized Fe3O4@NiO. The specific preparation process is as follows:
[0047] 1.2mmol of Fe3O4 and 1.0mmol of NiCl2·6H2O were added to 60mL of distilled water, and five groups of experiments were prepared after dispersion; 0.015mol, 0.030mol, 0.045mol, 0.060mol, and 0.075mol of ammonia water (1 drop / second) were slowly added thereto respectively; after the addition was completed, the mixture was stirred at room temperature for 30min, and then heated to 70℃ under mechanical stirring (400 rpm) and reacted for 4.0h respectively. After the reaction was completed, magnetic separation was performed, and the bottom product was washed with distilled water 3 times and freeze-dried for 24h. The dried powder was ground and placed in a muffle furnace and calcined at 400℃ for 2h to obtain Fe3O4@NiO nanoparticles ( Figure 4 ).
[0048] Example 5
[0049] The preparation method of Fe3O4@NiO nanoparticles in this embodiment comprises the following steps:
[0050] 1.2mmol of Fe3O4 and 1.0mmol of NiCl2·6H2O were added to 60mL of distilled water, and after dispersion, 0.060mol of ammonia water (1 drop / second) was slowly added thereto; after the addition was completed, the mixture was stirred at room temperature for 30min, and then heated to 70℃ and reacted for 4h under mechanical stirring (400 rpm). After the reaction was completed, magnetic separation was performed, and the bottom product was washed 3 times with distilled water and freeze-dried for 24h. The dried powder was placed in a muffle furnace and calcined at 400℃ for 2h to obtain Fe3O4@NiO nanoparticles ( Figure 5). It can be seen that the synthesized Fe3O4@NiO has a uniform morphology and is flower-like ( Figure 5 ac). Since the contrast of TEM images is related to the atomic number of the elements, the core-shell structure can be distinguished according to the contrast. At the same time, in the Fe3O4@NiO composite material, Fe3O4 acts as an endogenous magnetic core, giving the material ferromagnetism; the shell layer composed of NiO nanosheets contains a large amount of Ni 2+ ions, and can be directly used to separate target proteins without surface functionalization modification. The corresponding element surface distribution map shows that Fe is mainly distributed in the middle of the Fe3O4@NiO composite material, corresponding to the Fe3O4 nanocore; while the distribution of Ni and O elements corresponds to the flower-like structure of NiO ( Figure 5 df).
[0051] Figure 6 The XRD spectra, thermogravimetric (TG) curves, and FTIR spectra of Fe3O4, Fe3O4@Ni(OH)2, and Fe3O4@NiO are shown below. The diffraction peaks at 2θ=30.5°, 35.8°, 43.5°, 53.9°, 57.4°, and 62.9° are attributed to the (220), (311), (400), (422), (333), and (440) crystal plane diffraction of Fe3O4 (PDF No.19-629); this confirms that the corresponding synthesized product is indeed Fe3O4. The synthesized Fe3O4@NiO nanocomposite material shows similar diffraction peaks attributed to Fe3O4 ( Figure 6 a), and XRD peaks at 2θ = 37.2°, 43.2°, 62.9°, 75.4°, 79.4°, and 79.5°, which are attributed to the (101), (012), (110), (113), (202), and (006) crystal plane diffraction of NiO (see PDF No. 44-1159). This confirms that the corresponding synthetic product is a Fe3O4@NiO nanocomposite material. In addition, in order to further explore the phase changes during the synthesis reaction, we performed XRD characterization on the reaction intermediates. The corresponding diffraction peaks at 2θ = 33.1°, 38.5°, 52.1°, 59.1°, 62.7°, and 70.5°, respectively, are attributed to the (100), (101), (102), (110), (111), and (103) crystal plane diffraction of Fe3O4@Ni(OH)2 (PDF: 14-0117). This indicates that the intermediate of the synthesis reaction is Fe3O4@Ni(OH)2. Figure 6 The TG curve shown in b shows that Fe3O4@Ni(OH)2 loses water at 230-300℃ and transforms into Fe3O4@NiO. Figure 6 As can be seen from c, at 589cm -1 The absorption peak at 3632 cm is the Fe-O stretching vibration peak.-1 The absorption peak at 809cm is the Ni-OH stretching vibration peak, while the absorption peak at 809cm -1 and 798cm -1 The absorption peak at corresponds to Ni-O stretching vibration. This indicates that when the synthesis reaction system contains weakly alkaline ammonia water, its Ni 2+ Can be used with OH - The Ni(OH)2 is combined to form Ni(OH)2 and deposited on the Fe3O4 nanocore; and after calcination in a muffle furnace, Ni(OH)2 loses water to form NiO, thereby forming a NiO coating on the surface of the Fe3O4 nanocore.
[0052] The chemical states of the main elements in Fe3O4@NiO nanocomposites were analyzed by X-ray photoelectron spectroscopy (XPS). Figure 7 The XPS spectrum of Fe3O4@NiO (a) and the XPS spectra of O1s (b), C1s (c), Fe 2p (d) and Ni 2p (e) are given. The XPS spectrum of Fe3O4@NiO shows that it is composed of Fe, O, Ni, C and other elements ( Figure 7 a) From Figure 7 b It can be seen that the O1s peaks at 529.3eV, 531eV, and 532.4eV are attributed to the oxygen atoms of Fe3O4@NiO. 1 / 2 The spectrum peaks can be fitted into a double peak at 726.3eV and 724.6eV, while the Fe 2p 3 / 2 The spectrum peaks can be fitted as double peaks at 711.6eV and 714.2eV ( Figure 7 d). This indicates that the synthesized Fe3O4@NiO nanoadsorbent contains both Fe 2+ and Fe 3+ ; and Fe 2+ and Fe 3+ All of them correspond to the endogenous magnetic core Fe3O4. The endogenous magnetic core Fe3O4 of Fe3O4@NiO nano-adsorbent maintains its original crystal structure after high-temperature calcination at 400℃ in a muffle furnace, and does not transform into Fe2O3. Figure 7 It can be seen that Fe3O4@NiO shows Ni 2p peaks at 873.5eV and 855.7eV and satellite peaks at 879.7eV and 861.8eV, respectively (corresponding to Ni 2+ ). This indicates that Fe3O4@NiO contains NiO and high-spin Ni 2+ ions, and it can also be proved that the synthesized product is Fe3O4@NiO nanoparticles.
[0053] The magnetic susceptibility of Fe3O4 and Fe3O4@NiO was measured to be 140.21emu / g and 87.67emu / g ( Figure 8 a). The corresponding N2 adsorption-desorption curve of Fe3O4@NiO nanocomposite conforms to the type IV adsorption-desorption curve ( Figure 8 b). This indicates that the Fe3O4@NiO nanocomposite has a mesoporous structure; and its average pore size is about 12.7nm ( Figure 8 c) This porous structure is conducive to the subsequent adsorption and separation of the target protein.
[0054] Application Examples
[0055] (1) Adsorption performance of Fe3O4@NiO nanoparticles on His-tagged fusion proteins
[0056] a. The NiO coating layer in the Fe3O4@NiO nanoparticles has a targeted binding ability to His-tagged proteins and can be used to quickly separate His-tagged fusion proteins, so it can also be called Fe3O4@NiO nanoadsorbent. A series of adsorption experiments were conducted using His-tagged GFP of different concentrations as an example to evaluate the adsorption capacity of Fe3O4@NiO nanoadsorbent for His-tagged proteins. The specific test process is as follows:
[0057] Taking His-tagged GFP protein as an example, the saturated adsorption capacity of Fe3O4@NiO nanocomposites for His-tagged protein was determined. 0.02g of Fe3O4@NiO nanocomposites were weighed and placed in a 2mL microcentrifuge tube (EP tube), washed three times with Tris-HCl buffered saline (TBS buffer), and 1.50mL of His-tagged GFP protein solutions with concentrations of 0.20mg / mL, 0.40mg / mL, 0.60mg / mL, 0.80mg / mL, 1.00mg / mL and 1.20mg / mL were added thereto respectively; the mixed solution was placed in a silent reverberator and incubated at 4℃ for 1.5h; after the incubation, it was separated on a magnetic stand, the supernatant was aspirated, and the concentration of the remaining His-tagged GFP protein in the supernatant after the incubation was measured by UV-visible spectrophotometry (wavelength 280nm). The adsorption performance of Fe3O4@NiO nanoadsorbent on the target protein was calculated using formula (1):
[0058]
[0059] Where: C e (mg / mL) is the concentration of His-tagged GFP protein remaining in the tube after the Fe3O4@NiO incubation; C0 (mg / mL) is the concentration of His-tagged GFP protein in the tube before the Fe3O4@NiO incubation; Qe (mg / g) is the adsorption capacity of Fe3O4@NiO nanoadsorbent for His-tagged GFP protein; Q m (mg / g) is the maximum adsorption capacity of Fe3O4@NiO nanoadsorbent.
[0060] Fig. 9 The adsorption data of Fe3O4@NiO nanoadsorbent on His-tagged GFP protein, adsorption amount-time curve, and pseudo-first-order kinetic model and pseudo-second-order kinetic model simulation analysis results. It can be seen that the adsorption of His-tagged GFP by Fe3O4@NiO first increases with the increase of protein concentration and then remains unchanged; when the protein concentration increases to 1.0 mg / mL, its adsorption reaches saturation, and its maximum adsorption capacity is 65.83 mg / g ( Fig. 9 a); the corresponding time to reach adsorption equilibrium is about 60min ( Fig. 9 b).
[0061] In addition, the adsorption kinetics of Fe3O4@NiO nanoadsorbent on His-tagged protein (taking His-tagged GFP protein as an example) was studied, and a pseudo-first-order kinetic model was used for it ( Fig. 9 c) and pseudo-second-order kinetic model ( Fig. 9 d) Fitting analysis to determine the time required for the target protein to reach adsorption equilibrium. The specific process of adsorption kinetic analysis is as follows: weigh 12 portions of 0.02g of Fe3O4@NiO nanocomposites and place them in 2mL EP tubes, wash them with TBS solution three times; add 1.50mL of His-tagged GFP protein solution with a concentration of 1.00mg / mL; place the mixed solution in a silent reverberator and incubate at 4℃ for different times (5min, 10min, 15min, 20min, 25min, 30min, 40min, 50min, 60min, 70min, 80min and 90min). After the incubation, place the mixed solution on a magnetic stand for magnetic separation, aspirate the supernatant, and measure the concentration of His-tagged GFP protein remaining in the supernatant after incubation with a micro-spectrophotometer (wavelength 280nm). The pseudo-first-order kinetic equation (Equation 2) and pseudo-second-order kinetic equation (Equation 3) are as follows:
[0062] ln(Q e -Q t )=-k1t+lnQ e Equation 2
[0063]
[0064] Where: Qe (mg / g) and Q t (mg / g) is the equilibrium adsorption capacity of Fe3O4@NiO for His-tagged GFP protein and the adsorption capacity at time t; k1(min -1 ) and k2(g·mg -1 ·min -1 ) are the pseudo-first-order and pseudo-second-order kinetic constants, respectively. Fig. 9 c and 9d show the kinetic analysis results of Fe3O4@NiO nanoadsorbent adsorbing His-tagged GFP protein. It can be seen that the corresponding adsorption data are more consistent with the pseudo-second-order kinetic model. 2 =0.999, which is higher than the R based on the pseudo-first-order kinetic model. 2 =0.995.
[0065] b. Select different target proteins for universality, recycling and other performance tests. The specific test process is as follows:
[0066] In order to verify the universality of Fe3O4@NiO nanoadsorbent for His-tagged proteins and its application in the actual separation and purification of mixed proteins, three His-tagged fusion proteins were selected: His-tagged PYR1-LIKE 3 (denoted as His-tagged PYL3), His-tagged Karrikin Insensitive 2 (denoted as His-tagged KAI2) and His-tagged green fluorescent protein (denoted as His-tagged GFP) for separation and purification experiments. The target proteins were obtained by overexpression in Escherichia coli and fragmentation. The crude protein extract was used for SDS-PAGE experiment, and the captured proteins were subjected to immunoblotting experiment (Western blot analysis).
[0067] The specific steps of separation and purification are as follows: weigh 3 portions of 0.02g of Fe3O4@NiO nanoadsorbent in parallel, place them in microcentrifuge tubes respectively, add 0.003g of His-tagged PYL3 Escherichia coli lysate, 0.018g of His-tagged KAI2 Escherichia coli lysate, and 0.009g of His-tagged GFP Escherichia coli lysate respectively; incubate at 8°C for 5min, 30min and 90min respectively; after magnetic separation, retain the precipitate and wash the precipitate with buffer solution to obtain Fe3O4@NiO / His-tagged PYL3, Fe3O4@NiO / His-tagged KAI2, and Fe3O4@NiO / His-tagged GFP complexes respectively. The captured His-tagged fusion proteins were eluted with 600 μL imidazole solution (500 mmol / L) and subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) experiments to investigate its universality for different His-tagged fusion proteins. In addition to the electrophoretic bands corresponding to the target protein, no electrophoretic bands of other impurity proteins were observed ( Fig.10 ac), showing good universality. At the same time, the target protein ( Fig.10 df). It can be seen that Fe3O4@NiO nanoadsorbent has good separation and purification ability for His-tagged fusion protein, and has good application prospects in the actual separation and purification of mixed proteins.
[0068] (2) Cyclic performance
[0069] The recycling performance of Fe3O4@NiO nano-adsorbent for His-tagged proteins is crucial in practical applications. Therefore, this study was conducted, and the specific experimental process is as follows: 0.02 g of Fe3O4@NiO nano-composite material was weighed and placed in a microcentrifuge tube, and 1.50 mL of His-tagged GFP protein solution with a concentration of 1.00 mg / mL was added; after incubation at 4°C for 90 minutes, magnetic separation was performed, and the concentration of the remaining His-tagged GFP protein in the supernatant was quantitatively detected. At the same time, the nano-magnetic beads were washed with imidazole and buffer solution, and the precipitate was collected, and 1.5 mL of the same His-tagged GFP protein solution was added thereto. The above steps were repeated 5 times to investigate the recycling performance of Fe3O4@NiO nano-composite material in the separation of His-tagged GFP protein. After 5 cycles of use, Fe3O4@NiO nano-adsorbent still has a good separation effect on the target protein, and the separation capacity is higher than 80% ( Fig.11 b) and extremely high specific recognition ability ( Fig.11a), which indicates that the prepared Fe3O4@NiO nanoadsorbent has good specificity and recycling performance for the target protein and has good market application prospects.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing flower-like NiO nanomagnetic beads, characterized in that: The steps are: (1) Disperse Fe3O4 and NiCl2·6H2O in distilled water, add ammonia water, stir at room temperature and then stir and heat to react, separate the reaction solution and collect the bottom product; (2) The bottom product of step (1) is washed, dried and then calcined to obtain flower-like NiO nanomagnetic beads, namely Fe3O4@NiO nanoparticles.
2. The method for preparing flower-like NiO nanoparticles according to claim 1, characterized in that: In the step (1), the molar ratio of NiCl2·6H2O to Fe3O4 is 1:(0.3-1.4); 0.005-0.03 mol Fe3O4 is added per liter of distilled water.
3. The method for preparing flower-like NiO nanoparticles according to claim 2, characterized in that: For every 1 mmol of NiCl2·6H2O, 0.015-0.075 mol of aqueous ammonia should be added.
4. The method for preparing flower-like NiO nanoparticles according to claim 2, characterized in that: The stirring and heating reaction in step (1) is carried out at a temperature of 25-90° C. and a time of 0.5-6 h.
5. The method for preparing flower-like NiO nanoparticles according to claim 4, characterized in that: The calcination temperature in step (2) is 380-400°C and the calcination time is 2-3 h.
6. Flower-like NiO nanomagnetic beads prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the flower-like NiO nanomagnetic beads according to claim 6 in separating and purifying His-tagged fusion proteins.
8. The use of the flower-like NiO nanomagnetic beads according to claim 7 in separating and purifying His-tagged fusion proteins, characterized in that: The separation and purification steps are: adding flower-like NiO nanomagnetic beads to the mixed protein, incubating and magnetically separating to separate the flower-like NiO nanomagnetic beads bound with the His-tagged fusion protein; and then eluting with an eluent solution to obtain the separated and purified His-tagged fusion protein.
9. The use of the flower-like NiO nanomagnetic beads according to claim 8 in separating and purifying His-tagged fusion proteins, characterized in that: The mass ratio of the flower-like NiO nanomagnetic beads to the mixed protein is 1:(0.015-0.09).
10. The use of the flower-like NiO nanomagnetic beads according to claim 8 in separating and purifying His-tagged fusion proteins, characterized in that: The incubation temperature is 4-8°C and the incubation time is 5-90 min.
Citation Information
Patent Citations
Spherical porous Fe3O4 / MnO2 supercapacitor material and preparation method thereof
CN105895387A
Preparation method and application of composite magnetic materials of CuO@NiO core-shell structure
CN107376824A
Nanoparticles with flower-like core-shell structure and preparation method thereof
CN109502653A
Method for preparing BiOBr with different morphologies through selective regulation and control and application
CN117000271A
KR20240055572A